Academic High Achievers Versus Low Achievers: Divergent Views Of Academic Environment Among Bangladeshi Undergraduate Medical Students - Bhattacharjee, Sharmista; Chakraborty, Rivu Raj; Hossain, Mohammad Arif (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: The academic environment refers to the atmosphere which influences learning experiences and academic achievements. Assessing the students’ perception of academic environment is crucial for progress of institution and academic success. This study aims to compare the perceptions of high acheivers and low acheivers to find out variations in perceptions between two groups. Materials and methods: This cross sectional study included 25 students from each phase of MBBS course who volunteered to participate. The means and standard deviations were calculated for each subscales and total DREEM. Unpaired t test was used to compare the variations in perceptions between two groups. Results: The high achievers perceived stimulating teaching, clear learning objectives, social ease, relaxed classroom environment, disappointment and fatigue. The low achievers perceived irritation, anger and ridicule but received good feedback and support for stress. Both groups reported cheating as problem. The high achievers were found to have significantly higher mean scores in SPT (p=0.04), SPL (p=0.045), SASP (p=0.02), SPA (p=0.04), SSSP (p=0.02) and total DREEM score (p=0.002). Conclusion: This study identified areas of concern for both groups that can guide strategic reforms for creating supportive academic environment to improve academic success. JCMCTA 2025 ; 36 (1) : 18-24